2015
DOI: 10.1103/physrevd.91.044017
|View full text |Cite
|
Sign up to set email alerts
|

I-Love relations for incompressible stars and realistic stars

Abstract: In spite of the diversity in the equations of state of nuclear matter, the recently discovered I-Love-Q relations [Yagi and Yunes, Science 341, 365 (2013)], which relate the moment of inertia, tidal Love number (deformability) and the spin-induced quadrupole moment of compact stars, hold for various kinds of realistic neutron stars and quark stars. While the physical origin of such universality is still a current issue, the observation that the I-Love-Q relations of incompressible stars can well approximate th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(72 citation statements)
references
References 44 publications
13
59
0
Order By: Relevance
“…Therefore, these relations can be considered as universal only for sufficiently stiff stars. Thus, our analytical form of the I-Love relation (or the multipolar moment-Love relations) further supports the proposal reported in Sham et al (2015); Chan et al (2015Chan et al ( , 2016.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, these relations can be considered as universal only for sufficiently stiff stars. Thus, our analytical form of the I-Love relation (or the multipolar moment-Love relations) further supports the proposal reported in Sham et al (2015); Chan et al (2015Chan et al ( , 2016.…”
Section: Introductionsupporting
confidence: 91%
“…Its physical origin is certainly an interesting issue. It has been observed and proved in the cases of the modified Tolman model and self-bound stars, which both possess non-zero surface mass density, that the I-Love relation is stationary in the incompressible limit (Chan et al 2014;Sham et al 2015;Chan et al 2015Chan et al , 2016. Along a similar line of thought, using our perturbation solutions to the tidal Love numbers and the mass moments, we have established in the present paper that the I-Love relation is stationary with respect to arbitrary density changes in the incompressible limit, and generalised the stationarity to cases where l 2 (see Section 8.2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Testing the validity of the I-Love-Q relations offers another possibility for testing the equation of state. As it has been demonstrated [32][33][34], the universality of the I-Love-Q relations comes from properties of the equation of state that are related to the fact that the equation of state for compact objects is close to being incompressible. Deviations from being incompressible would change the different relations and in principle could also introduce some spin dependence.…”
Section: I-love-qmentioning
confidence: 99%
“…The I-Love-Q and I-Love relations, respectively, were investigated for incompressible and realistic stars; it was shown that the EoS-independent behaviour of the I-Love-Q relation can be attributed to its incompressible limit (Sham et al 2015;Chan et al 2015). Moreover, these relations were also calculated by Pani (2015) for exotic objects such as thin-shell gravastars at zero temperature, without assessing their validity.…”
Section: Introductionmentioning
confidence: 99%